Power Spectral Analysis of Heart Rate Variability in Female Rheumatoid Arthritis Patients - Jahan, Kawser; Begum, Noorzahan; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2012)
Background: Association of increased cardiovascular morbidity and higher sympathetic activity in patients with Rheumatoid arthritis (RA) has been recognized. Heart rate variability (HRV) is a useful measure to assess sympatho-vagal balance. Objective: To assess autonomic nerve function status in patients with Rheumatoid Arthritis (RA) by HRV analysis. Methods: This cross sectional study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka from January to December 2010. Sixty female RA patients aged 18-50 years were included in the study group. They were enrolled from the Out Patient Department of Rheumatology Wing of the Department of Medicine, BSMMU, Dhaka. For comparison age matched thirty apparently healthy females were also studied as control. The HRV parameters were recorded by a Polyrite machine. For statistical analysis independent sample t test was used. Results: Mean resting pulse rate, diastolic blood pressure and mean systolic blood pressure were higher in rheumatoid arthritis patients in comparison to those of healthy control. Mean values of LF power, LF norm and LF/ HF were significantly higher (p<0.001) & TP and HF power, HF norm were significantly lower (p<0.001) in RA patients in comparison to those of healthy control. Conclusion: This study may conclude that sympathetic activity was higher with lower parasympathetic activity along with shifting of sympathovagal balance towards sympathetic predominance in patients with rheumatoid arthritis. DOI: http://dx.doi.org/10.3329/jbsp.v7i1.11153 J Bangladesh Soc Physiol. 2012, June; 7(1): 8-12